Association of blood pressure level with nonalcoholic fatty liver disease in nonhypertensive population: Normal is not the new normal. Issue 29 (July 2016) - Qian, Lin-Yan; Tu, Jian-Fei; Ding, Ya-Hui; Pang, Jie; Che, Xian-Da; Zou, Hai; Huang, Dong-Sheng
Abstract : Abstract: The functional crosstalk between nonalcoholic fatty liver disease (NAFLD) and hypertension has been reported by some literatures; however, in nonhypertensive individuals, there is no article describes the characteristic of NAFLD. In this study, we aimed to determine the strength of the association between NAFLD with normal blood pressure (BP) in nonhypertensive individuals. This cross-sectional study was conducted in the sixth Affiliated Hospital of Wenzhou Medical University, from October 2007 to December 2011. In brief, 24, 200 subjects were enrolled to participate in the survey. Among those subjects, there were 5305 enrolled subjects, those with filling the diagnostic criteria for NAFLD (21.9%; 4803 males and 502 females). Nonhypertension was identified in 17, 403 (71.9%; 8179 males and 9224 females). The PR% of NAFLD for the systolic blood pressure (SBP) in quartiles 1 to 4 was 10.83, 12.55, 20.38, and 19.97. SBP, diastolic blood pressure (DBP), sex, age, glutamic pyruvic transaminase, glutamic oxaloacetic transaminase, fasting plasma glucose, uric acid, triglyceride, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol are closely associated with the risk for NAFLD. SBP (odds ratio [OR]: 1.092, 95% confidence interval [CI]: 1.030–1.158; P  < 0.05) and DBP (OR: 1.157, 95%CI: 1.094–1.223; P  < 0.05) were found to be independent risk factors for NAFLD. Our analysis indicates that BP is significantly associated with NAFLD in nonhypertensive individuals; SBP and DBP are found to be independent risk factors for NAFLD.